Sustainable Animal and Aquatic Foods (SAAF) science program inception workshop - Njenga, Geoffrey; Hurt, Chris (International Livestock Research Institute, 2025)
The Sustainable Animal and Aquatic Foods (SAAF) science program held its internal inception workshop in Tunis, Tunisia, from February 18–20, 2025, with optional field trips on the 21st February. The event brought together around 60 participants, including representatives from various centers, areas of work, underlying initiatives, and key staff from the emerging Project Management Unit (PMU). The workshop aimed to build a cohesive SAAF team with a shared understanding of the program’s goals and approaches, identify concrete integration strategies, and define country-level and global work plans. Discussions covered program components, engagement with other science programs, and the inception plan, including the Plan of Work and Budget (PoWB). The event also facilitated team building, set key priorities for the program’s launch, and established a clear action plan to finalize the inception phase and begin implementation.